How to Kill a Dragon : Aspects of Indo-European Poetics. - Watkins, Calvert (Oxford University Press, 1995)
A demonstration of the continuity of poetic formulae in Indo-European languages from Old Hittite to medieval Irish. Using the comparative method, the traditional poetic formulae can be reconstructed back to the original common languages, thus revealing the tenacity of the poetic tradition.